Enhancing Health Outcomes Through City Information Modeling (CIM): A Case Study of Sydney, Australia - Adibhesami, Mohammad Anvar; Karimi, Hirou; Sepehri, Borhan; Parvanehdehkordi, Amirmohamad (Springer, 2024)
A case study was conducted in Sydney, Australia, to explore the potential of City Information Modeling (CIM) in improving health outcomes. Sydney is a diverse and populous city with over 5 million residents, featuring a range of urban environments, from densely populated inner-city areas to sprawling suburban neighborhoods. The case study focused on how urban interventions impact health outcomes in Sydney, collecting data on the city’s physical, social, and economic characteristics, as well as health outcomes. By using this data, a 3D model of the city was created. CIM has been used for this model, which was utilized to evaluate how various urban interventions, such as the addition of green spaces or improvements to public transportation, affect health outcomes. The results of the case study analysis demonstrate that CIM can effectively identify areas of the city that are most vulnerable to health risks and assess the impact of urban interventions on health outcomes. However, the study also highlighted the need for better data collection and analysis, improved collaboration between public health professionals and urban planners, and the development of more sophisticated CIM tools. Overall, the case study in Sydney has shown that CIM has great potential for improving health outcomes. To realize this potential, it is crucial to have the right tools and collaboration, enabling CIM to effectively identify areas of the city most in need and evaluate the impact of interventions on health outcomes. © The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2024.
Keywords: City Information Modeling (CIM); Geographic Information Systems (GIS); Health Outcomes; Urban Interventions